Multicentric high grade oligodendroglioma: a rare entity. (2nd November 2019) - Vats, Atul; Amit, Amit; Doshi, Paresh
Abstract: A 74 year old male presented with 1 month history of weakness in right upper limb and motor aphasia for 15 days. Magnetic resonance imaging (MRI) of the brain showed three discrete ring enhancing lesions. An image guided awake craniotomy and biopsy of a lesion was performed. The histopathological examination revealed it to be a grade III Oligodendroglioma. This was a rare case of multicentric high grade oligodendroglioma has never been reported in literature. We report such a case with relevant review of literature.